GOVERNANCE OF CREATIVITY: ANALYZING POWER DYNAMICS IN UEES SCHOOL OF ARTS' CULTURAL PROCESSES - Rodriguez, Gabriela Lopez (Current Journal of Humanities, Arts and Social Sciences (CJHASS), 2023)
This paper examines the influence of power relations on management in cultural-artistic processes within an organization of artistic education. The study was conducted at the School of Arts at the Universidad de Especialidades Espíritu Santo (UEES) in Ecuador. A qualitative approach was used, and data was collected through interviews, observations, and document analysis. The findings suggest that power relations play a significant role in the management of cultural-artistic processes. These relations can be either positive or negative, and they can influence the way that decisions are made, the way that resources are allocated, and the way that people interact with each other. The study also found that a diversity of roles can emerge in cultural-artistic processes, and that these roles can be influenced by power relations.